2016
DOI: 10.1016/j.ijinfomgt.2016.05.025
|View full text |Cite
|
Sign up to set email alerts
|

A survey on Test Suite Reduction frameworks and tools

Abstract: Abstract-Software testing is a widely accepted practice that ensures the quality of a System under Test (SUT). However, the gradual increase of the test suite size demands high portion of testing budget and time. Test Suite Reduction (TSR) is considered a potential approach to deal with the test suite size problem. Moreover, a complete automation support is highly recommended for software testing to adequately meet the challenges of a resource constrained testing environment. Several TSR frameworks and tools h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…So, the primary objective behind optimization process is to find out the representative test set which has a minimal number of test cases that covers the whole program and find the same number of faults as original test suite did. A complete survey of the different techniques and critical investigation on different tools used for test suite optimization can be found in the research work by Yoo and Harman [6] and Khan et al [7]. After study we found that using only single criteria we cannot improve the optimization process effectively [12].…”
Section: Background and Related Workmentioning
confidence: 92%
“…So, the primary objective behind optimization process is to find out the representative test set which has a minimal number of test cases that covers the whole program and find the same number of faults as original test suite did. A complete survey of the different techniques and critical investigation on different tools used for test suite optimization can be found in the research work by Yoo and Harman [6] and Khan et al [7]. After study we found that using only single criteria we cannot improve the optimization process effectively [12].…”
Section: Background and Related Workmentioning
confidence: 92%
“…In the context of software engineering, clustering has been used in the past, for reverse engineering and software maintenance tasks, with the aim to categorise software artifacts [22,23]. The concept of similarity is a fundamental building block for any clustering technique, as well as a key issue in various contexts, such as detecting cloned code [24,25,26,27], software plagiarism [28], or reducing test suite size in modelbased testing [29,30]. According to Walenstein et al [31], a workable common understanding for software similarity is as follows: "the degree to which two distinct programs are similar is related to how precisely they are alike."…”
Section: Reasons For Clusteringmentioning
confidence: 99%
“…Software testing is a widely used practice and is carried out to ensure the quality of software being developed and to ensure that the software is defect free. The Software testing process includes a number of phases such as test planning, test definition, test suite reduction [1], defect tracking and test closure activities [2]. While the test case execution phase is usually recursive and requires considerable testing time, cost and efforts.…”
Section: Introductionmentioning
confidence: 99%